1996
DOI: 10.1007/bf01718607
|View full text |Cite
|
Sign up to set email alerts
|

HA1 domain of influenza A (H3N2) viruses in Finland in 1989–1995: evolution, egg-adaptation and relationship to vaccine strains

Abstract: The HA1 gene sequences of 22 MDCK cell-derived influenza A (H3N2) strains, ten of their egg-derived counterparts and three vaccine strains were determined. Antigenic and sequence differences between the epidemic and vaccine strains were recorded, most striking in 1992/93; a minority of the amino acid differences in 1989-95 was involved in egg-adaptation. Changes in the assortment of amino acid substitutions produced during egg-adaptation of field strains may account for the difficulty encountered in isolating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Similar mutations in H1N1 swine flu isolates from the 1970 s increase growth in eggs and MDCK cells and reduce growth in swine [12]. Other groups have also demonstrated positive selective pressure on a variety of residues near the receptor binding site in H3N2 isolates, including variations at the same residues (186 and 194) [13-15] that we detected in our H1 S-OIV quasi-species. More recently, Glaser et al showed that a mutation at a nearby position (190) in the HA of the avian H1N1 virus that caused the 1918 pandemic was associated with this strain's adaptation to humans [16].…”
Section: Resultssupporting
confidence: 72%
“…Similar mutations in H1N1 swine flu isolates from the 1970 s increase growth in eggs and MDCK cells and reduce growth in swine [12]. Other groups have also demonstrated positive selective pressure on a variety of residues near the receptor binding site in H3N2 isolates, including variations at the same residues (186 and 194) [13-15] that we detected in our H1 S-OIV quasi-species. More recently, Glaser et al showed that a mutation at a nearby position (190) in the HA of the avian H1N1 virus that caused the 1918 pandemic was associated with this strain's adaptation to humans [16].…”
Section: Resultssupporting
confidence: 72%
“…The amino acid sequence of the HA 1 of L phenotype viruses was identical to that of A/Beijing/353/89 as determined by [16] (GeneBank L76036). The entire HA 1 and HA 2 sequences of S and Mo viruses were identical and differed from L viruses by a single base substitution (A 814 →T) in HA 1 , giving rise to amino acid substitution Asn to Ser at residue 246.…”
Section: Resultsmentioning
confidence: 82%
“…Egg adaptation has been associated with a number of sequence changes that alter potential N-linked glycosylation sites on the HA, including the site at residue 246 of H3 subtype viruses [25-27] although loss of this site from particular H3 field strains was not associated with adaptation to growth in eggs [16]. In general terms, amino acid substitutions associated with egg-adapted variants cluster around the receptor-binding site on the HA molecule [28] and are likely to increase binding to Sia(α2,3)Gal moieties on cells of the chicken embryo chorio-allantoic membrane, the site of influenza virus replication in chicken eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if lectin-mediated defenses decline in the elderly, an effect of glycosylation on virulence could be masked. Recently, Pyhälä et al (37) reported the loss of potential glycosylation sites (not associated with egg adaptation) at residues 246 and 278 of the HA of certain H3N2 field strains isolated in Finland in 1994 to 1995. Loss of glycosylation sites from HA was also found among H1N1 strains isolated in Finland and elsewhere in Europe in the period 1988 to 1993 (36) and among H1N1 strains isolated in 1983 to 1984 from specimens collected during persistent infection of an immunodeficient child (40).…”
Section: Discussionmentioning
confidence: 99%